SELF-ASSEMBLED POLYELECTROLYTE COMPLEX OF SILK FIBROIN WITH ALGINATE AS DRUG DELIVERY MODEL - Cahya Eka Darma, Gita
Silk Fibroin (SF) and Alginate (ALG) are biomaterial that have therapeutic efect in wound dressing which is hemostatic, and the ability upon absorption of wound exudates. Natural therapeutic agents has many advantages than the use of chemical synthetic drugs, so that making it a good alternative in the medication. This research aims to make delivery model for wounds dressing in the form of fiber membrane results from polyelectrolyte complexation (PEC) through coacervation method. SF from silkworm cocoons (Bombyx mori Linn) used as polycations agent, ALG as polyanions agent and Chloramphenicol (CHL) as drug model. Characterization of PEC fiber membranes are conducted with analysis of the functional groups (FTIR), crystallinity degree (XRD), thermal properties (DSC), microscopic (SEM). Then, the study continued to the measurement of coacervation yield, swelling test, and in-vitro drug release test. SDS PAGE was used to verify the protein. This research has gained SF with better new characteristics, in order to obtain the appropriate PEC fiber membrane as delivery models for the treatment of skin wounds. PEC fiber membrane is a modified version from hydrogel-forming of SF—ALG coacervate. SF in the membrane is in the stable conformation structure (Silk If) with a proper cystallinity degrees of SF and the SF—ALG electrostatic crosslinking, so this fiber membrane can swelling or dissolve depending on the pH of the system. Characterization analysis of the membrane shown that the electrostatic bonds occurs between SF with ALG, polymorphic forms of the protein fibroin and crystallinity degree of SF and membrane can be controlled to determine the final result of the membrane. PEC fiber membrane is responsive to pH, at pH < 3 swelling occurs while at pH > 3—5,5 it dissolved, this condition could be adjusted to the pH condition of the site released. The swelling profile increased from pH 0 Alpto pH 3 with the lowest percentage is (F3) and the highest is (92). The CHL release profile of Fl—F3 respectively are 91,33; 98,88; 81,94% during 30 minute. The fastest drug release profile obtained from the formula with a higher amount of ALG, and otherwise on the formula that SF amounts is higher then the release is slower, this ratio can determine the type of release as required.